PERWUJUDAN NIALAI-NILAI DALAM KELEMBAGAAN NEGARA UNTUK MEMBENTUK PERATURAN - Watoni Noerdin (Muhammadiyah Law Review Journal, 2021)
Formation of the legislation is a requirement in the development of national law which can only be achieved if supported by a good method, which is binding on all institutions authorized to make Regulations. Indonesia is a country that has a legal obligation to carry out the development of a good national law, which is done in a planned, sustainable, and integrated into the national legal system. The concept of the establishment of laws and regulations in Indonesia includes several concepts, namely the concept of the establishment of legislation must be in accordance with State law concept of Pancasila. In addition, the concept of the establishment of legislation that either must prioritize the protection of Human Rights. The concept of the establishment of legislation that both must put forward the principle of equality before the law. The concept of the establishment of legislation that either should be in accordance with the principles of the formation of legislation predetermined by law. Henceforth, the concept of the establishment of law established by legal authority, elected by the people in a democracy.